Regulation of Ca2+ signaling in mast cells by tyrosine-phosphorylated and unphosphorylated non-T cell activation linker - Dráberová, Lubica; Shaik, Gouse Mohiddin; Volná, Petra; Heneberg, Petr; Tůmová, Magda; Lebduska, Pavel; Korb, Jan; Dráber, Petr (Journal of immunology (Baltimore, Md., 2007)
Engagement of the FcepsilonRI in mast cells and basophils leads to a rapid tyrosine phosphorylation of the transmembrane adaptors LAT (linker for activation of T cells) and NTAL (non-T cell activation linker, also called LAB or LAT2). NTAL regulates activation of mast cells by a mechanism, which is incompletely understood. Here we report properties of rat basophilic leukemia cells with enhanced or reduced NTAL expression. Overexpression of NTAL led to changes in cell morphology, enhanced formation of actin filaments and inhibition of the FcepsilonRI-induced tyrosine phosphorylation of the FcepsilonRI subunits, Syk kinase and LAT and all downstream activation events, including calcium and secretory responses. In contrast, reduced expression of NTAL had little effect on early FcepsilonRI-induced signaling events but inhibited calcium mobilization and secretory response. Calcium response was also repressed in Ag-activated cells defective in Grb2, a major target of phosphorylated NTAL. Unexpectedly, in cells stimulated with thapsigargin, an inhibitor of the endoplasmic reticulum Ca(2+) ATPase, the amount of cellular NTAL directly correlated with the uptake of extracellular calcium even though no enhanced tyrosine phosphorylation of NTAL was observed. The combined data indicate that NTAL regulates FcepsilonRI-mediated signaling at multiple steps and by different mechanisms. At early stages NTAL interferes with tyrosine phosphorylation of several substrates and formation of signaling assemblies, whereas at later stages it regulates the activity of store-operated calcium channels through a distinct mechanism independent of enhanced NTAL tyrosine phosphorylation.
Keywords: Molecular Sequence Data; nádorové buněčné linie; Rats; sekvence aminokyselin; receptory IgE; Receptors, IgE; mastocyty; Phosphorylation; vápník; adaptorové proteiny signální transdukční; Calcium Signaling; Cell Line, Tumor; antigeny CD98 - lehké řetězce; Amino Acid Transport System y+; tyrosin; krysa rodu Rattus; Calcium; Intracellular Fluid; Tyrosine; vápníková signalizace; zvířata; Adaptor Proteins, Signal Transducing; Amino Acid Sequence; intracelulární tekutina; transportní systém aminokyselin y+; Mast Cells; fosforylace; molekulární sekvence - údaje; Fusion Regulatory Protein 1, Light Chains; Animals